Development of grid-side converter-based FRT control and protection in a grid-connected solar photovoltaic park system under different control modes - Nithya, C.; Roselyn, J. Preetha (Frontiers in Energy Research, 2022)
In a grid-connected solar photovoltaic system, voltage dips on the grid side, increased grid current, and overshoot in the inverter’s dc-link voltage are all noticed during grid disturbances. The grid code stipulates that in order to protect the cascaded power converter systems from high currents and overvoltages, the solar PV system disconnects from the grid anytime the voltage level at PCC falls below a particular standard nominal value. This study proposes combined GSC-based fault ride-through (FRT) and protection control strategies which can provide independent real and reactive power control for the inverter for effective FRT in photovoltaic parks interconnected with a large power system during grid faults. The proposed approach operates in three modes—voltage control, power factor control, and reactive power control modes. The developed protection modules in the PV system consist of over/undervoltage protection, voltage sag detection, and overcurrent detection. The inverter-fed real–reactive power control technique limits grid overcurrent by modifying active power injection into the grid and stabilizes grid voltage during faults by injecting reactive current. The performance of the proposed FRT and protection control strategy is studied through the simulation of 75 MW PV park in the EMTP platform and the experimental setup of a 5 kVA grid-connected inverter-fed solar PV system. The simulation results and hardware discussion presented in this study validate the performance of the proposed FRT scheme in comparison with conventional control schemes during grid faults.